The Use of Duolingo Application to Enhance Junior High School Students’ Speaking ability - Windya Windya; Intan Ayu Enjeli Silalahi; Iwa Maulana; Ikrar Dwi Febrina Sarumaha; Juliana Juliana (Edumaspul: Jurnal Pendidikan, 2023)
The study explored the use of the Duolingo application in junior high school language education to improve speaking ability. The research used a quasi-experimental design, dividing students into two groups: one receiving traditional instruction and the other using Duolingo as a supplementary tool. Data was collected through speaking assessments, student surveys, and classroom observations. The results showed a significant improvement in speaking ability among the Duolingo group compared to the traditional instruction group. The application's interactive features, gamified elements, and accessibility make it an engaging and effective learning experience. Student feedback also indicated increased motivation and interest in language learning. The study highlighted the potential of integrating Duolingo into language education and its implications for curriculum design, technology role in language learning, and addressing diverse learning styles. It provides valuable insights into the effectiveness of using Duolingo as a supplementary tool for enhancing speaking ability in junior high school language education. Further research is recommended to explore the long-term impact and scalability of Duolingo in diverse educational settings.